Trends in the Development of Social Responsibility of Business Organizations in Kazakhstan - A. K. Temirgalinova; A. A. Titkov; S. Zh. Ibraimova (Экономика: стратегия и практика, 2023)
The article is devoted to developing the institutional framework for the social responsibility of business in the Republic of Kazakhstan. The object of the study is business organizations represented by small, medium, and large enterprises. The subject of the study is the organizational and economic foundations of social responsibility. The purpose of this study is to analyze the trends of social responsibility, identify problems, priorities for building this institution. The following methods were used as research methods: analytical, statistical, computational-analytical, and dialectical-search methods. The study is based on data for the strategic period 2016-2020, separate data for 2010 and 2015. The study showed that the participation of enterprises in the development of the social sphere is in its infancy. The mechanisms of social responsibility are characteristic of large enterprises, an important role belongs to the state. Social responsibility does not meet international standards. Social responsibility-oriented standards are not used enough in the business environment. In the labor market, there are tendencies to reduce real wages, which reduces the degree of social responsibility. The formed mechanisms of social responsibility do not create conditions for developing the social sphere, or the development of human potential, which does not contribute to economic growth. In the future, the organizational and economic mechanisms of social responsibility of large corporations, small and medium-sized businesses at the micro, meso and macro levels should be improved. The study was discussed at scientific seminars at Toraigyrov University with the participation of economists, representatives of the state and businesses.